Rancang Bangun Robot Humidifier Beroda Untuk Menjaga Kelembapan Udara Ideal Mencegah Terinfeksi Bakteri Berbasis Mikrokontroler - Fifto Nugroho; Ananda Tri Oktavianthi; Alexius Ulan Bani (Forum Kerjasama Pendidikan Tinggi, 2022)
Cases of patients infected with bacteria still exist today, this is due to the lack of public attention to the reasonableness of clean air in the room. Air humidity is needed by living things, the impact of the absence of air humidity levels such as dryness and air turbidity that is too high will cause uncomfortable conditions for living things in the surrounding environment and will increase bacteria and viruses. Currently the estimated idea to overcome its spread prevention is to design a tool that can work automatically by utilizing embedded system technology as a trigger component to get the input value of air humidity levels and can communicate with the ATMega328 AVR microcontroller board for further processing to carry out its work. The reason for this research is to design and build a wheeled humidity robot that is equipped with a mist generator component as an essential part to generate steam and automatically runs humidifying the air in every room that needs it